Strengthening Family Resilience Through Local Wisdom: Pulang Ka Bako Type of Marriage in Minangkabau - Warman, Arifki Budia; Zulkifli, Zulkifli; Yustiloviani, Yustiloviani; Nabilah, Wardatun; Hayati, Riska Fauziah (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This paper aims at explaining the background of the persistence of Pulang ka Bako marriage in Lasi area and its correlation to family resilience. This research is field research. The Minangkabaunese still carry out the tradition of Pulang ka Bako marriage (marrying the daughter of father’s female sibling) in Minangkabau community, especially in Lasi area. This marriage is considered the ideal type of marriage in Minangkabau. The data sources were obtained from the result of interview with married couples, traditional leaders, and religious leaders. The collected data were then reduced, presented, and concluded. This result showed that the background of Pulang ka Bako marriage was the community’s understanding that this type of marriage can guarantee the development and maintenance of inheritance, kinship social relations, and preservation of traditions and customs. This tradition can build family resilience in the terms of economic and social, and it strengthens cultural resilience as well. From the perspective of maqashid al-sharia, Pulang ka Bako marriage does not only bring benefit to the individual but also to the family. Besides fulfilling the elements of hifzun nasl (preserving offspring), hifzul mal (managing assets), and hifzul 'irdh (maintaining honor), Pulang ka Bako also fulfills the elements of tahqiqul sakn wal mawaddah wa rahmah (realizing the sense of peace, love, and compassion) and tanzimul janibul mali (managing family finances). It can be concluded that Pulang ka Bako type of marriage has fulfilled the objectives of Islamic law and is capable of being one of the solutions to family resilience issues.